2017
DOI: 10.1186/s13007-017-0212-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Bayesian functional regression models with interactions for predicting wheat grain yield using hyper-spectral image data

Abstract: BackgroundModern agriculture uses hyperspectral cameras that provide hundreds of reflectance data at discrete narrow bands in many environments. These bands often cover the whole visible light spectrum and part of the infrared and ultraviolet light spectra. With the bands, vegetation indices are constructed for predicting agronomically important traits such as grain yield and biomass. However, since vegetation indices only use some wavelengths (referred to as bands), we propose using all bands simultaneously a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 22 publications
2
50
0
Order By: Relevance
“…A recent study developed statistical models to assess hyperspectral wavelength  environment interactions in HTP, incorporating genomic and pedigree G  E interactions [78]. Although little GP accuracy was achieved, important hyperspectral wavelength  environment interactions were observed, demonstrating that GS coupled with HTP can be a powerful tool applied to early-generation testing of a large number of selection candidates.…”
Section: Prospects For Enhanced Use Of Gs In Plant Breedingmentioning
confidence: 99%
“…A recent study developed statistical models to assess hyperspectral wavelength  environment interactions in HTP, incorporating genomic and pedigree G  E interactions [78]. Although little GP accuracy was achieved, important hyperspectral wavelength  environment interactions were observed, demonstrating that GS coupled with HTP can be a powerful tool applied to early-generation testing of a large number of selection candidates.…”
Section: Prospects For Enhanced Use Of Gs In Plant Breedingmentioning
confidence: 99%
“…Radiation reflected from leaves can provide information about the internal composition of the leaf (Blackburn, 2007;Jacquemoud et al, 1996;Jacquemoud & Baret, 1990). Reflectance over a broad range of narrow and contiguous wavelength bands, termed hyperspectral reflectance, is increasingly used to predict plant or crop traits including water status (Gutierrez, Reynolds, & Klatt, 2010;Sims & Gamon, 2003); photosynthetic metabolism (Ainsworth, Serbin, Skoneczka, & Townsend, 2014;Barnes et al, 2017;Serbin, Dillaway, Kruger, & Townsend, 2012;Silva-Pérez et al, 2018); leaf mass per area (LMA; Asner & Martin, 2008;Ecarnot, Compan, & Roumet, 2013); concentrations or contents of nitrogen (N), lignin, and photosynthetic pigments (Martin & Aber, 1997;Yendrek et al, 2017); and grain yield (Montesinos-López, Montesinos-López, Montesinos-López, Cuevas, et al, 2017;Weber et al, 2012). ; Atkin et al, 2015;Reich, Walters, Ellsworth, et al, 1998;Reich, Walters, Tjoelker, Vanderklein, & Buschena, 1998;Ryan, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…For the aerial method, the highest correlations (0.33 and 0.44) were reached on days 45 and 41, respectively. To assess the usefulness of canopy coverage data in the early stages of the vegetative growth, the information from days [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] (for the four data sets) was included in the prediction models, and the results were compared with those obtained using canopy information from the whole season. …”
Section: Relationship Between Canopy Coverage Data and Grain Yieldmentioning
confidence: 99%
“…Dealing with high-throughput phenotypic information, several authors [11][12][13] have shown improvements in predictive ability with the inclusion of these sources of information in the models for wheat and maize. Montesinos-Lopez et al [14] showed that accounting for the band (hyper-spectral image data)-by-environment interaction also improved yield predictability in wheat when compared with those models that did not include this component in the models.…”
Section: Introductionmentioning
confidence: 99%